Strategi Pembelajaran Program Pelayanan Individual Siswa ABK di SD Inklusi - Devi Laili Maesaroh; Naili Azkiya Sari; Erika Oktaviana Putri; Muhammad Nofan Zulfahmi (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This research aims to evaluate learning strategies in individual service programs for students with Special Needs (ABK) in inclusive elementary schools (SD). The method used is literature study, by examining various sources from journals, books and scientific articles. The research results show that effective individual learning strategies include curriculum adjustments, application of various learning methods, and collaboration between class teachers and accompanying teachers. In addition, support from the school environment and family was also identified as an important factor in the success of this program. The implementation of individual service programs aims to meet the special needs of each ABK student, so that they can reach their maximum potential in an inclusive education environment. It is hoped that this research can make a significant contribution to the development of inclusive education practices in Indonesia.